2019
DOI: 10.3906/kim-1903-36
|View full text |Cite
|
Sign up to set email alerts
|

The solvatochromism and electronic structure of(E)-2-(2-hydroxystyryl)quinolin-8-ol

Abstract: The (E)-2-(2-hydroxystyryl)quinolin-8-ol (abbreviated as HSQ) molecule was synthesized and characterized. The ESIPT, solvatochromism properties, electronic structure, and ground and excited electric dipole moments of this molecule were measured using absorption and fluorescence spectra recorded in 13 different solvents. Its electronic structure via electronic transitions was investigated to find the quantitative values of solvatochromism properties by LSER calculations. The ESIPT mechanism was clarified; groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Nucleus independent chemical shift (NICS) was introduced by Schleyer and coworkers as a simple and efficient probe for aromaticity [37] . Thereafter, many studies have been published via computation of NICS to determine aromaticities of the related systems [38,39] . The stability of metal complexes can also be determined by investigation of chelatoaromaticity [40] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleus independent chemical shift (NICS) was introduced by Schleyer and coworkers as a simple and efficient probe for aromaticity [37] . Thereafter, many studies have been published via computation of NICS to determine aromaticities of the related systems [38,39] . The stability of metal complexes can also be determined by investigation of chelatoaromaticity [40] .…”
Section: Resultsmentioning
confidence: 99%
“…[37] Thereafter, many studies have been published via computation of NICS to determine aromaticities of the related systems. [38,39] The stability of metal complexes can also be determined by investigation of chelatoaromaticity. [40] According to Zborowski et al aromaticity of ligands is enhanced upon complexation with cations.…”
Section: Chemistryselectmentioning
confidence: 99%
“…In terms of ESIPT research, the most common heterocyclic compounds that have been developed are 2-(2-hydroxyphenyl)benzimidazole (HBI), 2-(2-hydroxyphenyl)benzoxazole (HBO), and 2-(2-hydroxyphenyl)benzothiazole (HBT), as well as their many derivatives. Besides these compounds, quinoline [ 2 ], benzophenone [ 3 ], flavone [ 4 ], anthraquinone [ 5 ], benzotriazole [ 6 ], quinoxaline [ 7 , 8 ], salicylidenaniline [ 9 ], pyrazole [ 10 ], and imidazolone [ 11 ] have been found to have ESIPT emission. Menges and his colleagues, on the other hand, recently found that, in addition to the ring systems indicated above, imidazole with a carbonyl in the C-2 position (CIM: C-2 carbonyl imidazole; CIN: C-2 carbonyl indole) and an indole ring with an oxalate functionality also emit ESIPT [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%